Manifestations of Selfhood and Otherness in Indian Schools of Photography: رشا اكرم موسى (Al-Academy, 2021)
The current research addressed (the manifestations of selfhood and otherness in Indian schools of photography) through studying the concept of selfhood and otherness and their manifestations in Indian miniatures scenes for the period (1625-1790). The researcher, in the first chapter, sought to clarify the research problem, importance, and the need for it, in addition to the objective of the study represented by the following: "how did selfhood and otherness manifest in the Indian schools of photography?". The researcher, then, concluded the aforementioned chapter by defining the terms that have direct relation to the title and the objectives of the research. As for the second chapter, it consists of an overview for the theoretical framework and the indicators. Thus it consists of two sections, the first section addresses the concepts of the selfhood and otherness. The second section addresses the technical characteristics of the Indian schools of photography. The third chapter is dedicated to observing the research community and the tool which included gathering the information. An intentionally chosen sample has been used consisting of (4) photographic works that covered the research limitations by adopting the analytic descriptive approach in order to analyze it according to the axes of the analysis tool adopted by the researcher. As for the fourth chapter, it included the results of the research including: The Indian photographs addressed the concept of selfhood and achieving it with the presence of the other in another way not limited to the real objective reality, but rather in the subconscious and dreams, that what a person feels and thinks about in his subconscious of buried wishes might be manifested through the dreams to reinforce the achievement of the selfhood with the presence of the otherness, as in the model (2) of the sample. Then the conclusions, through which the possibility of achieving the research objectives by the tool designed by the researcher, including: Selfhood and otherness have manifested in the photographic works of the Indian school of photography, through the expression of what realizes the self through the other in varying proportions, that selfhood was not absolutely represented and neither was the otherness.Then come the recommendations, suggestions and a list of references and appendices